INNOVATIVE DIRECTION OF DEVELOPMENT OF THE SERVICES SECTOR AS A FACTOR OF ECONOMIC GROWTH - Nasirov Dilshod Farhadovich (International Journal of Economic Integration and Regional Competitiveness, 2024)
Innovative direction of development of the service sector plays an important role in stimulating economic growth. Economic changes and technological innovations in the service sector can lead to increased employment and improved living standards, increase labor productivity, improve the quality of services and create new opportunities for entrepreneurship. The article describes the results of innovative development that allow achieving a high standard of living in the service sector. At present, one of the main components of the post-industrial economy is the dynamic development of the service sector. It is services that act as the main product of labor, the consumption of services is becoming the predominant way to meet the needs of the population. In the general structure of the economy, there is a sharp increase in the role of service industries, which marks the transition of society's development from the industrial stage to the next stage of development, different from the previous stage.